A Single Process Model of the Same-Different Task - Harding, Bradley (Université d'Ottawa / University of Ottawa, 2018)
The Same-Different task has a long and controversial history in cognitive psychology. For over five decades, researchers have had many difficulties modelling the simple task, in which participants must respond as quickly and as accurately as possible whether two stimuli are the “Same” or “Different”. The main difficulty in doing so stems from the fact that “Same” decisions are much faster than can be modelled using a single process model without resorting to post-hoc processes, a finding since coined the fast-same phenomenon. In this thesis, I evaluate the strengths and shortcomings of past modelling endeavours, deconstruct the fast-same phenomenon while exploring the role of priming as its possible mechanism, investigate coactivity as a possible architecture underlying both decision modalities, and present an accumulator model whose assumptions and parameters stem from these results that predicts Same-Different performance (both response times and accuracies) using a single-process, a finding deemed near impossible by Sternberg (1998).
Keywords: Same-Different task; comparison task; matching task; priming; fast-same phenomenon; coactivity; cognitive architecture; modelling